Community stories of resilience building in ASEAN strengthening community resilience through peer-to-peer learning. (Quezon City Oxfam, 2017)
Asia is vulnerable to more frequent and severe disasters due to the rapid rise of natural hazards, extreme weather events, and the impacts of climate change. ASEAN’s Declaration on Institutionalizing the Resilience of ASEAN and its Communities and Peoples to Disasters and Climate Change recognizes this, and its vision of resilience sets out to achieve ‘a more resilient future by reducing existing disaster and climate-related risks, preventing the generation of new risks, and adapting to a changing climate through the implementation of economic, social, cultural, physical, and environmental measures which address exposure and vulnerability, and thus strengthen resilience.’

The Strengthening Community Resilience through Peer-to-Peer Learning Project focused on communities and the actions that they are taking to enhance their resilience. The case studies presented here were gathered through four learning journeys that took place in the project’s focus countries: Myanmar, the Philippines, Thailand, and Viet Nam. Together, the studies comprise a set of community-led initiatives that, with ASEAN’s continued support, can enable the region to achieve its inclusive vision of resilience.
01 THE ROLE OF CLIMATE RESILIENT AGRICULTURE IN COMMUNITY RESILIENCE -- 02 PARTICIPATORY GOVERNANCE AND URBAN RESILIENCE -- 03 THE ROLE OF WOMEN’S ECONOMIC EMPOWERMENT IN COMMUNITY RESILIENCE -- 04 SAFE SCHOOLS AND COMMUNITY RESILIENCE -- 05 THE ROLE OF ELDERLY PEOPLE IN COMMUNITY RESILIENCE -- 06 THE ROLE OF COMMUNITY CHAMPIONS AND COLLABORATIONS IN COMMUNITY RESILIENCE -- 07 LOCAL PARTICIPATORY PLANNING FOR COMMUNITY RESILIENCE -- 08 LIVELIHOODS DIVERSIFICATION FOR COMMUNITY RESILIENCE -- 09 LOCAL ENERGY PLANNING FOR COMMUNITY RESILIENCE -- 10 THE ROLE OF SMEs IN COMMUNITY RESILIENCE
UCWS-3501g donated by Nathalie Lourdes Africa-Verceles.
SW-11362G and SW-11361G donated by OXFAM Philippines.
Keywords: Community development -- Southeast Asia -- Case studies; Emergency planning -- Citizen participation -- Southeast Asia